Native and introduced parasitoids in the biocontrol of Dryocosmus kuriphilus in Veneto (Italy)1. (19th July 2016) - Colombari, F.; Battisti, A.
Abstract : The invasive gallmaker Dryocosmus kuriphilus is a threat to chestnut stands and it is necessary to control it in order to maintain a satisfactory nut yield. A preliminary evaluation of the native natural enemies emerging from the galls, mainly parasitoids associated with native cynipid gallmakers, revealed that they were not able to contain the pest. Consequently, a classical biological control programme using Torymus sinensis started in 2010, with almost 500 releases being made in 6 years. The parasitoid achieved a satisfactory level of control of the pest over a period of time shorter than expected based on literature related to other countries. The success in the study area might be explained by specific traits intrinsic to T. sinensis, such as its high spread capability via stratified dispersal (i.e. a combination of short‐ and long‐distance flights), together with a large availability of host galls and limited competition with other parasitoids.